The state and the development prospects of the Lubusz cluster initiative "The Lubusz Wine and Honey Route" = Stan i perspektywy rozwoju lubuskiej inicjatywy klastrowej "Lubuski Szlak Wina i Miodu" - Piątyszek-Pych, Alina (Zielona Góra: Faculty of Economics and Management Press)
The concept of economic clusters, which are an effective way of seeking synergy effects resulting from cooperation of individual entities, became a synonym for the success of the economy of the region. The prospect of potential benefits for enterprises and regions, resulting from functioning of the bunches, encourages their potential participants to engage in creation and development of cluster structures. Such deliberate and organized effort of crucial players of the cluster, aimed at improvement in its competitiveness, is defined as a cluster initiative.
Keywords: klastry; inicjatywa klastrowa; gospodarka regionu; Lubuskie Region; przemysł winiarski; clusters; cluster initiative; Lubusz Voivodeship; wine industry